Healthcare support workers' lived experiences and adaptation strategies within the care sector during the COVID-19 pandemic. A meta-ethnography review. Issue 4 (2nd October 2022) - Kasdovasilis, Pavlos; Cook, Neil; Montasem, Alexander; Davis, Gershan
ABSTRACT: Support workers are an "invisible" part of the health sector often working during pandemics to support clients. This meta-ethnography screened 167 articles out of 211 results identifying 4 qualitative studies that explored the support worker's experiences during the COVID-19 pandemic. "Redundancy approach" was used to map non-essential criteria and the analysis was informed by the interpretative meta-ethnography method. Eight key themes identified from studies in UK and USA. The themes identified are: (1) job role; (2) marginalized profession; (3) impact of work; (4) concerns surrounding PPE; (5) transportation challenges; (6) level of support and guidance; (7) a higher calling and self sacrifice; (8) adaptation strategies. Adaptation strategies include purchasing their own masks, to policy and agency adaptation, cleaning, talk walks, meetings with colleagues or within the company. The adaptation strategies aim at tackling emotional distress and raise the level of appreciation that society or organizations show to the support workers.